Evaluation of Differences in the Quality of Frozen Mango Blocks from Different Varieties - MAO Erjie, LI Zhongxin, CHEN Jianle, CHEN Shiguo, YE Xingqian, CHENG Huan (Shipin Kexue, 2025)
In this study, fruit blocks of 10 mango varieties such as ‘Xiaotainong’ and ‘Guiqimang’ were rapidly frozen in liquid nitrogen. After thawing, their texture characteristics, taste characteristics, volatile flavor composition, total soluble solids (TSS) content, and total phenolic content were determined using a texture analyzer, an electron tongue, headspace solid-phase microextraction combined with gas chromatography-mass spectrometry (HS-SPME-GC-MS), respectively, with the aim of exploring the freezing adaptability and application potential of different mango varieties and selecting mango varieties suitable for making frozen fruit blocks. The results showed significant differences in freezing adaptability and quality characteristics among varieties. ‘Xiaotainong’ and ‘Guiqimang’ mangoes exhibited high contents of TSS and total phenols as well as high sweetness levels. Conversely, ‘Daguifei’ mangoes had the highest juice loss rate, reflecting poor freezing adaptability and low palatability after thawing. The hardness, elasticity, and chewiness of ‘Xiaotainong’ ‘Guiqimang’ and ‘Daqingmang’ mangoes were outstanding after thawing, while ‘Daguifei’ and ‘Xiaoguifei’ mangoes had the poorest texture, showing severe softening after thawing. ‘Xiaotainong’ mangoes had the largest number and amount of volatile compounds, (280.96 ± 26.02) mg/kg, with terpenes being the predominant ones, contributing to its strong fruity aroma. The results of electronic tongue analysis and sensory evaluation corroborated that ‘Xiaotainong’ performed exceptionally well in terms of appearance, texture, taste, and aroma, being the most palatable variety. In conclusion, ‘Xiaotainong’ mangoes, with high sweetness, rich aroma, and excellent texture, is suitable for the development of frozen mango blocks for direct consumption or as an ingredient for premium foods. The findings provide theoretical support for the selection of mango varieties and the development of frozen mango products.